2013
DOI: 10.1115/1.4025561
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Rise in Electroosmotic Flow of Typical Non-Newtonian Biofluids Through Rectangular Microchannels

Abstract: Electroosmosis is the main mechanism for flow generation in lab-on-a-chip (LOC) devices. The temperature rise due to the Joule heating phenomenon, associated with the electroosmosis, may be detrimental for samples being considered in LOCs. Hence, a complete understanding of the heat transfer physics associated with the electroosmotic flow is of high importance in design and active control of LOCs. The objective of the present study is to estimate the temperature rise and the thermal entry length in electroosmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Here m e is the electroosmotic parameter. The analytical solution of above Equation (14) subject to boundary conditions ∂Φ ∂y = 0, at y = 0 and Φ = 1, at y = h(x) is obtained as;…”
Section: Potential Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here m e is the electroosmotic parameter. The analytical solution of above Equation (14) subject to boundary conditions ∂Φ ∂y = 0, at y = 0 and Φ = 1, at y = h(x) is obtained as;…”
Section: Potential Distributionmentioning
confidence: 99%
“…Hadigol et al [13] considered the microscopic mixing characteristics of the power-law fluid in electroosmosis. Yavari et al [14] demonstrated an increase in EOF temperature of bio-fluids (non-Newtonian) via microchannel. Furthermore, Bandopadhyay et al [15] studied electroosmosis and peristalsis in microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the exploitation of the electroosmotic flow actuation method, where an electric field is applied to transport an electrolyte solution through narrow channels in the presence of an electrical double layer (EDL) across the electrolyte-substrate interface. Extensive studies on the hydrodynamic behavior of electroosmotic flows have been reported using biofluids [1][2][3][4], polymeric solutions [5,6] and colloidal suspensions [7][8][9]. Liu et al [3] modelled a way to pump non-conducting fluids and biofluids which couldn't be put directly in an electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, the biofluids that are used for analysis and detection schemes are blood or DNA solutions, which shows viscoelastic behavior and have different flow characteristics than that of Newtonian fluids (Park and Lee [2008a,b]). In addition to this, particular interest was also shown towards the thermal characteristics of electroosmotic flow of non-Newtonian fluids (Sadeghi et al [2010(Sadeghi et al [ , 2011, Escandon et al [2011Escandon et al [ , 2013, Sanchez et al [2013], Yavari et al [2013], Goswami et al [2016]). Sadeghi et al [2011] have studied the heat transfer due to a fully developed electroosmotic flow of Phan-Thien-Tanner (PTT) and FENE-P viscoelastic fluids under the Debye-Huckel linearization and shown that the viscous dissipation effect is important for low values of viscoelastic parameter and Debye layer thickness.…”
Section: Introductionmentioning
confidence: 99%